UPAYA MENINGKATKAN AKHLAK ANAK USIA DINI (5-6 TAHUN) MELALUI PEMBELAJARAN TEMATIK BERBANTUAN MEDIA AUDIOVISUAL DI PAUD AL-KAMAL LAUT DENDANG - Siti Aminah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACT This classroom action research conducted to determine the moral improvement of early childhood (5-6 years) through thematic learning aided audiovisual media. The research location is Al-Kamal school of early childhood of Education Foundation Al-Kamal Laut Dendang. While the subject of this research is the B group students that consist of 20 students.The method that was used in this research is qualitative method with a classroom action research (PTK) model. The actions carried out in three cycles. Each cycle consists of several stages: planning, action, observation and reflection. Data collected through test instruments, observation sheet and documentation. The data that have been obtained was analyzed descriptively with the steps: data Reduce, presented the data and appealing conclusions.The results of this study indicate that the child's knowledge of Morals at pre-action to cycle one from 15 people got BM categoris with a value of 2.39 (less than 60%), and MM categories of 5 people with a value of 2.60 (60-69).Reduced to 9 people who received BM categories increased to be 11 people MM categories. Morals knowledge of children in cycle 2 to cycle 3 from 7 people got BM categories with 2.39 value (less than 60%) and amounted to be 8 people got MM categories with 2.60 value (60-69).The next category of BSH amounted to 5 people with 2.80 value (70-79), increased to 5 people who got BSH category, and BSB 15 with 3:20 value (80-100).Morals of children's skills from pre-action to cycle 1 of 11 people got BM categories with 2.39 value (less than 60%) and MM 9 people with 2.60 value (60-69).. Reduced to 5 people who received BM categories and MM category increased to 15 people with 2.60 value (60-69).Morals skills of children in cycle 2 to cycle 3, 4 people got BM categories with 2.39 value (less than 60%), and amounted 7 people MM categories  with 2.60 value  (60-69), who got the next BSH category amounted to 9 people. Increased to 3 people who got BSH category with 2.80 value (70-79), and 17 people who got BSB categories with 3.20 value (80-100).The response of the children on the knowledge and skills of the character in the pre-action to cycle 1 is good enough, because the children have started to understand the character's behavior.Furthermore, the response of moral knowledge and skills of the children from cycle 2 to cycle 3 good and fun because the children already understand the behavior of good character. Therefore, the children are motivated to do a good moral behavior in the classroom and out of the classroom.  Key Words: Morality, Thematic Learning, Audiovisual Media